2018
DOI: 10.1063/1.5048697
|View full text |Cite
|
Sign up to set email alerts
|

Multilayer phosphorene quantum dots in an electric field: Energy levels and optical absorption

Abstract: Triangular and hexagonal multilayer phosphorene quantum dots with armchair and zigzag terminations are investigated with the orthogonal tight-binding model. The effect of increasing the number of layers is revealed. The obtained results show that in a small size multilayer quantum dot the edge states are as sensitive to the out-of-plane external electric fields as the edge states in a single layer dot to the in-plane external electric fields. The investigated optical absorption cross sections show that armchai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…However, the hBN quantum dots have been hardly investigated, especially in comparison with the graphene and other 2D material based quantum dots (for instance Refs. [61][62][63][64][65][66][67][68][69][70][71][72][73][74][75][76][77] etc.). Nevertheless, some studies on structural stability, magnetic, optical and adsorption properties can be found in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…However, the hBN quantum dots have been hardly investigated, especially in comparison with the graphene and other 2D material based quantum dots (for instance Refs. [61][62][63][64][65][66][67][68][69][70][71][72][73][74][75][76][77] etc.). Nevertheless, some studies on structural stability, magnetic, optical and adsorption properties can be found in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, y-directed field (parallel to the zigzag edge) will provide an oscillating effect on the low energy molecular orbitals at the zigzag edge. While the filed applied in x-direction (perpendicular to the zigzag edge) will increase the small E g between the edge states in GNR4-W3-L4 and decrease the wide band gap between the surface extended states in doped GNR4-W3-L4-OBO similar to its effect on hexagonal flakes with zigzag edges reported in [56]. Similarly, the y-field in the latter case decreases the band gap.…”
Section: Doping and Electric Fieldmentioning
confidence: 64%
“…Phosphorene quantum dots [36][37][38][39][40][41][42][43] in the form of small flakes have been extensively studied, in particular from the point of view of optical properties. In this work we consider a clean electrostatic confinement that keeps the confined electrons off the edge of the flake.…”
Section: Introductionmentioning
confidence: 99%